2020
DOI: 10.3390/jpm10030140
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Driven Approach to Carrier Screening for Common Recessive Diseases

Abstract: Genetic screening is an advanced tool for reducing recessive disease burden. Nowadays, it is still unclear as to the number of genes or their variants that are necessary for effective screening. This paper describes the development of a carrier screening custom panel for cystic fibrosis, phenylketonuria, alpha-1 antitrypsin deficiency, and sensorineural hearing loss consisting of 116 variants in the CFTR, PAH, SERPINA1, and GJB2 genes. The approach is based on the cheapest and fastest method, on using a small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
10
0
3
Order By: Relevance
“…Moreover, this whole-exome study demonstrated the overrepresentation of several disease-causing variants for Mendelian disorders, such as phenylketonuria (PAH, rs5030858), Wilson's disease (ATP7B, rs76151636), factor VII deficiency (F7, rs36209567), and the kyphoscoliosis type of Ehlers-Danlos syndrome (FKBP14, rs542489955). For the Russian population, however, pathogenic variant frequencies were reported mostly for relatively small cohorts including patients and their families and targeted at specific genes and disorders, for example, familial hypercholesterolemia (Meshkov et al, 2021;Miroshnikova et al, 2021); cystic fibrosis, phenylketonuria, alpha-1 antitrypsin deficiency, and sensorineural hearing loss (Kiseleva et al, 2020;Petrova et al, 2020); cardiomyopathy (Marakhonov et al, 2019;Zaklyazminskaya et al, 2019;Kulikova et al, 2021;Shestak et al, 2021); and breast and ovarian cancer (Brovkina et al, 2018;Solodskikh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this whole-exome study demonstrated the overrepresentation of several disease-causing variants for Mendelian disorders, such as phenylketonuria (PAH, rs5030858), Wilson's disease (ATP7B, rs76151636), factor VII deficiency (F7, rs36209567), and the kyphoscoliosis type of Ehlers-Danlos syndrome (FKBP14, rs542489955). For the Russian population, however, pathogenic variant frequencies were reported mostly for relatively small cohorts including patients and their families and targeted at specific genes and disorders, for example, familial hypercholesterolemia (Meshkov et al, 2021;Miroshnikova et al, 2021); cystic fibrosis, phenylketonuria, alpha-1 antitrypsin deficiency, and sensorineural hearing loss (Kiseleva et al, 2020;Petrova et al, 2020); cardiomyopathy (Marakhonov et al, 2019;Zaklyazminskaya et al, 2019;Kulikova et al, 2021;Shestak et al, 2021); and breast and ovarian cancer (Brovkina et al, 2018;Solodskikh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There is an emphasis on the role of heterozygous carriers in AR disease that was the basis for the concept of premarital screening programs especially in consanguineous populations 26,27 . The concept is also included in prenatal diagnosis (PND) and preimplantation genetic diagnosis (PGD) for monogenic inherited disorders 28,29 , and expanded carrier testing (ECT), a term that can be extended to include screening for genes involved in complex or multigene disorders 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…В связи с этим всего за несколько лет количество научных проектов, проводимых в сотрудничестве с Биобанком, значительно увеличилось. Технологии биобанкирования и стандартизация всех этапов пробоподготовки и информационного сопровождения в виде баз данных позволяют проводить широкомасштабные генетические исследования [26][27][28][29]. Другой пример возрастающей важности биобанков как источника биообразцов необходимого количества и качества -это развитие протеомики, метаболомики, липидомики и других омикс-технологий, которые могут дать информацию о развитии и прогнозе заболеваний, а также о возможных реакциях на определенный образ жизни (питание и др.)…”
Section: результаты и обсуждениеunclassified